A Combined Effect of G-Quadruplex and Neuro-Inducers as an Alternative Approach to Human Glioblastoma Therapy - Pavlova, Galina; Kolesnikova, Varvara; Samoylenkova, Nadezhda; Drozd, Sergey; Revishchin, Alexander; Shamadykova, Dzhirgala; Usachev, Dmitry Y.; Kopylov, Alexey (Frontiers in Oncology, 2022)
Cancer cell reprogramming based on treatment with G-quadruplex, having antiproliferative power, along with small molecules able to develop iPSCs into neurons, could create a novel approach to diminish the chance of glioblastoma recurrence and circumvent tumor resistance to conventional therapy. In this research, we have tested several combinations of factors to affect both total cell cultures, derived from tumor tissue of patients after surgical resection and two subfractions of this cell culture after dividing them into CD133-enriched and CD133-depleted populations (assuming CD133 to be a marker of glioblastoma stem-like cells). CD133+ and CD133− cells exhibit different responses to the same combinations of factors; CD133+ cells have stem-like properties and are more resistant. Therefore, the ability to affect CD133+ cells provides a possibility to circumvent resistance to conventional therapy and to build a promising strategy for translation to improve the treatment of patients with glioblastoma.